Natural gas conversion VII : proceedings of the 7th Natural Gas Conversion Symposium, June 6-10, 2004, Dalian, China - Natural Gas Conversion Symposium 2004 : Dalian Shi, China); Bao, Xinhe; Xu, Yide.; ScienceDirect eBooks (Amsterdam ; Boston : Elsevier, 2004)
This volume contains peer-reviewed manuscripts describing the scientific and technological advances presented at the 7th Natural gas Conversion Symposium held in Dalian, China, June 6-10, 2004, and a FREE CD-rom. This symposium continues the tradition of excellence and the status as the premier technical meeting in this area established by previous meetings. The manuscripts have been divided into eight different topics, Industrial Processes, Economics, Technology Demonstration and Commercial Activities;, Production of Hydrogen from Methane, Methanol, and Other Sources; Production of Synthesis; Fischer-Tropsch Synthesis of Hydrocarbons; From Synthesis Gas to; Catalytic Combustion; From Natural Gas to Chemicals; Light Hydrocarbons; and Production and Conversion . These are the most interesting subjects in the utilization of natural gas with recent scientific innovation and technological advances. The book is of interest to all students and researchers active in utilization of natural gas. - This book contains the papers of the symposium that is considered to be the premier technical meeting in this area. - The chapters give an overview of the latest developments in utilization of natural gas. - Topics included in the book are: Industrial Processes, Economics, Technology Demonstration and Commercial Activities;, Production of Hydrogen from Methane, Methanol, and Other Sources; Production of Synthesis; Fischer-Tropsch Synthesis of Hydrocarbons; From Synthesis Gas to; Catalytic Combustion; From Natural Gas to Chemicals; Light Hydrocarbons; and Production and Conversion.
Industrial processes, economics, technology demonstration and commercial activities -- Production of hydrogen from methane, methanol, and other sources -- Production of synthesis gas -- Fischer-Tropsch synthesis of hydrocarbons -- From synthesis gas to chemicals -- Catalytic combustion -- From natural gas to chemicals -- Light hydrocarbons : production and conversion.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Synthetic fuels -- Congresses; Gasoline, Synthetic -- Congresses; Natural gas -- Congresses; TECHNOLOGY & ENGINEERING -- Chemical & Biochemical; Gasoline, Synthetic; Natural gas; Synthetic fuels; Gas conversion; Electronic books